Sustaining Culture among the Young Indonesian Generation - Dellarosa, Maretha; Muhimmah, Hitta Alfi; Julianto, Julianto; Wicaksono, Vicky Dwi; Sukartiningsih, Wahyu; Mulyani, Mulyani; Mizan, Saeful (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Teaching in a multicultural country such as Indonesia presents unique challenges. This paper examines how teachers envision diversity and how they build an inclusive learning environment in a multicultural classroom community. To address these questions, qualitative study was employed. Data collected included semi-structured interviews, journals, observations, class documentation, and relevant documents. In addition, the data gathered were analyzed thematically. This research requires the participation of two teachers who dedicated their time to teaching students in early childhood education. The study underscores various activities in teaching diversity to young generations that can inspire other teachers who want to foster a classroom environment where an individual's uniqueness is valued and nurtured. Also, several aspects of diversity are discussed.